KEMAMPUAN LITERASI DASAR PESERTA DIDIK KELAS II DI SD NEGERI SENDANGGUWO 01 KOTA SEMARANG - Daffa Harits Ariyadi; Muhardila Fauziah (STKIP Subang, 2026)
This research is motivated by the importance of basic reading literacy skills for elementary school students as a foundation for understanding various information and supporting the learning process. Reading literacy skills relate not only to the ability to read texts but also to the ability to comprehend reading, find information, evaluate reading, and develop reading habits. However, in practice, some students still experience difficulties in comprehending reading content and processing information from the texts they read. Therefore, this study aims to analyze the basic reading literacy skills of second-grade students at Sendangguwo 01 Public Elementary School, Semarang City. This study used a qualitative approach with field research. Data collection techniques used were observation, interviews, and documentation. Data sources included the principal, second-grade teachers, and second-grade students at Sendangguwo 01 Public Elementary School, Semarang City. Data validity was verified through source triangulation and technical triangulation. The results indicate that the basic reading literacy skills of second-grade students at Sendangguwo 01 Public Elementary School, Semarang City have developed quite well. Most students are able to read simple texts, understand the content, find information, answer questions based on the reading, and retell the content in their own words. Factors inhibiting basic reading literacy skills include differences in student reading ability, lack of independent reading habits, difficulty understanding information in reading, and limited literacy facilities. Supporting factors for basic reading literacy skills include the role of teachers in providing guidance, developing reading habits, student interest in literacy activities, school environmental support, and family involvement.